Integrative counselling skills in action - Culley, Sue; Bond, Tim , 1949- (SAGE counselling in action, 2011)
An exceptional, well-loved book that has been used to train thousands of students on counselling skills courses. This book guides the reader through the core counselling skills required for practice and demonstrates how to apply them in typical, everday settings